The Effectiveness Of The Apheresis Method On The Quality Of Trombosit Concentrat At UTD PMI Surabaya - Renata Primasari; Wahyu Wirahmayati (Universitas STRADA Indonesia, 2020)
Apheresis is obtained from one donor, donors are connected to a machine that can clean up blood and only take platelets. The remaining cells and blood plasma are then returned to the donor's body. The purpose of this study was to determine the effectiveness of apheresis methods on the quality of blood products in UTD PMI Surabaya. This type of research uses a post test only control design, which was conducted on November 1st, 2019 - March 30th, 2020 with a sample of 50 TC Apheresis and 50 TC conventional. The quality of blood products carried out by the apheresis method at UTD PMI Surabaya has met the quality standards that have been tested. While the quality of blood products that do not use the Apheresis method at UTD PMI Surabaya, there are 2 samples that do not meet the standards, 48 ​​other samples have met the standards